2018
DOI: 10.1002/asia.201801296
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalysts Derived from Unnatural α‐Amino Acids: Scope and Applications

Abstract: The organocatalytic properties of unnatural aamino acids are reviewed. Post-translational derivatives of natural a-aminoa cids include 4-hydroxy-l-proline and 4amino-l-proline scaffolds, and also prolineh omologues. The activity of synthetic unnatural a-amino acid-based organocatalysts, such as b-alkyl alanines, alanine-based phosphines, and tert-leucine derivatives, are reviewed herein. The orga-nocatalytic properties of unnatural monocyclic,b icyclic, and tricyclicproline derivatives are also reviewed. Sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 152 publications
(157 reference statements)
0
7
0
Order By: Relevance
“…From the biotechnological and biomedical point of view, NcAAs have found applications as a significant expansion of the building-block repertoire and/or as organocatalysts (Agirre et al, 2019), also in the manufacture of a wide range of pharmaceuticals (Patel, 2013;Narancic et al, 2019), or as linear and cyclic peptides (Blaskovich, 2016;Martin et al, 2018). Some of the commercial applications directly rely on the natural properties of peptide-containing NcAAs, such as several antibiotics.…”
Section: Biomedical and Biotechnological Applications Of Ncaasmentioning
confidence: 99%
“…From the biotechnological and biomedical point of view, NcAAs have found applications as a significant expansion of the building-block repertoire and/or as organocatalysts (Agirre et al, 2019), also in the manufacture of a wide range of pharmaceuticals (Patel, 2013;Narancic et al, 2019), or as linear and cyclic peptides (Blaskovich, 2016;Martin et al, 2018). Some of the commercial applications directly rely on the natural properties of peptide-containing NcAAs, such as several antibiotics.…”
Section: Biomedical and Biotechnological Applications Of Ncaasmentioning
confidence: 99%
“…6,[9][10][11][12] In particular, some of these MOFs could provide a suitable reaction environment through control of the aperture of the MOF cavities. 13 Amino acid and its derivatives, which are practical organocatalysts, 14 have been widely used for catalyzing asymmetry organic reactions, such as aldol, Michael addition and Mannich reaction. [15][16][17][18] Given the existence of regularly ordered chiral functionalities to provide high enantioselectivity, amino acids are anchored into the MOF cavities to generate a heterogeneous catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 In a number of other studies, the side chain amino group of this amino acid has been used as a functionalization site for attachment of moieties or peptide branching. [24][25][26][27] Due to the presence of the amino/ammonium group in the structure, it has been suggested that Amp can serve as a residue that endows peptides with pH-responsiveness. In a couple of proof-of-principle studies, the effect of the medium acidity has been demonstrated for Amp containing collagen mimicking peptides.…”
Section: Introductionmentioning
confidence: 99%